Seismic Behavior of Precast Buildings With Dissipative Connections - De Stefani, Lorenzo; Scotta, Roberto (Frontiers in Built Environment, 2021)
Recent earthquakes in southern Europe highlighted that the connections of cladding panels to R.C. frames in precast buildings had a major role in the structural collapse. For this reason, there is a urgent need for a review of the design methods for these connections as well as for an improvement in the manufacturing technology. This paper aims to assess the efficiency of dissipative panel-to-structure and roof connections in RC precast buildings. A parametric study, consisting in linear and non-linear analyses on one case-study building is performed. Different sensitivity analyses are performed varying their mechanical properties (i.e., stiffness, strength, and ductility) to analyse the behaviour of the CP/frame connections. The study focuses on dissipative connections with an elastic-plastic behaviour, placed between cladding panels (CPs) and frames in precast buildings with stacked horizontal cladding panels. The introduction of dissipative CP/frame connections implies the inclusion of panels in the global seismic resisting system. The “panels + frame” system highlights a high stiffness until the yield strength of the CP/frame connections is reached. The results, obtained from non-linear dynamic analyses (NLDAs), clearly show how the proposed connection improves the structural seismic performance. By contrast, this is no longer true for R.C. precast structures with flexible diaphragms, especially for intermediate columns, far from panels aligned to seismic action. In this case significant and unexpected axial forces arise on out-of-plane connections between panels and columns. The integration of an efficient diaphragm is essential to prevent these critical issues both on intermediate columns and CP/column connections: it enables the dissipative capacity of the “panels + frame” system and it significantly limits the forces and displacements of intermediate alignments. Unfortunately, the achievement of a rigid diaphragm is not always feasible in precast buildings. A possible alternative to activate dissipative capacities of the roof diaphragm with limited in-plane stiffness is the use of dissipative connections linking roof beams and main beams. The solutions described in this paper can be applied both in the design of new buildings and for the seismic upgrading of existing ones with easy-to-install and low-impact applications.